Analysis of the Uncertainty of Basic Wages in the Employment Agreement of PT X from the Perspective of Law No. 13 of 2003 on Manpower and DSN-MUI Fatwa No. 112/DSN-MUI/IX/2017 - Sima, Dwi; Sahliah, Sahliah (IHSA Institute, 2025)
An employment agreement is a legal instrument that underlies the bond between workers and employers, encompassing the rights and responsibilities of each party. One of the essential elements of the agreement is the basic wage, which serves as the foundation for calculating various wage components. Ambiguity in stipulating the basic wage often leads to negative effects, with serious implications for legal protection and legal certainty for workers. This research aims to examine the issue of ambiguity in determining the salary or basic wage in employment contracts at PT X, using the perspective of Law No. 13 of 2003 on Manpower and Fatwa No. 112/DSN-MUI/IX/2017. To complete this study, the author applies a normative juridical research method. The findings reveal that the absence of a detailed basic wage in the employment contract at PT X contradicts the provisions of Article 54 paragraph (1) letter e of Law No. 13 of 2003 on Manpower, as well as the principle of clarity of ujrah (wages) in an ijarah contract. Therefore, it is necessary to revise PT X’s employment contracts by specifying the basic wage components in detail and explicitly, as a form of legal certainty and legal protection for employees, in accordance with applicable legal regulations and sharia values